Determinación del potencial de rendimiento de grano de las variedades de arroz `Iniap 15´, `Iniap 16´, `f - 50´ y `f - 21´ en presencia del bioestimulante orgánico razormin - Palma Cedeño, Omar Ezequiel (2011)
In lands of Mr. Mauro Nuñez, located in km. 31 of the Durán route - Orange grove, Province of the Guayas; a test in the varieties of rice settled down `Iniap - 15', `Iniap - 16'; `F - 50' and `F - 21', proving different levels from fertilization to obtain grain yields of 8; 10 and 12 Ton/ha with the purpose of: to evaluate the agronómico behavior and grain yield of ls varieties of rice in the presence of the organic bioestimulante Razormin; to determine the appropriate program of chemical fertilization to manage to operate all the genetic potential of the tried varieties; and, economically to analyze the grain yield in function to the cost of the program of chemical fertilization. The experimental design denominated “complete Blocks” with factorial adjustment was used at random 3 x 4 in four repetitions; giving a total of twelve treatments, distributed randomly in each block. The experimental parcel was conformed by 12 separated rows of 6m of length to 0.25m, giving an area of 18m2; whereas, the useful area was of 12m2, that is to say, that was constituted by the 8 central rows.